THE CORRELATION BETWEEN KNOWLEDGE AND ATTITUDE WITH COMPLIANCE OF FE TABLET CONSUMPTION IN ANEMIA OF THE THIRD TRIMESTER PREGNANT WOMEN - Dwi Kurnia Purnama Sari; Masrufah (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Anemia in pregnancy increases the risk of miscarriage, premature birth, low birth weight, bleeding after delivery. Anemia can be prevented by consuming a balanced nutritious diet and giving 90 tablets of Fe during pregnancy. The purpose of this study was to determine whether there was a correlation between knowledge and attitude with adherence to Fe tablet consumption in pregnant women with anemia in the third trimester in the working area of ​​Merakurak Health Center. The research design used an observational analytic design with a cross-sectional approach. The sampling technique was simple random sampling. The population was 21 pregnant women with Third Trimester anemia in the working area of ​​the Merakurak Health Center and a sample of 20 people. The contingency coefficient test using SPSS 21 obtained a value of 0.036 (p<0.05) meaning there was a correlation between knowledge and compliance and the contingency coefficient test is 0.264 (p>0.05) meaning there was no correlation between attitude and compliance. So it was suggested for more intensive socialization and supervision by families with a control card for Fe tablet consumption in pregnant women with anemia in the third trimester.